ANALYSIS OF ALKALINE AND ALKALINE EARTH METALS IN STANDARD SAMPLES BY LIQUID ELECTRODE PLASMA OPTICAL EMISSION SPECTROMETER - Hidayanto, Eko; Yamamoto, Takashi; Kawai, Jun (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT—Sodium, potassium and calcium in standard sample solution were analyzed with a portable analyzer of liquid electrode plasma optical emission spectrometer (LEP-OES) to assess its validity for quantitative analysis. Reproducibility and sensitivity were investigated using different disposal sample chip and applied voltage. ln the applied voltage of 800 V, there is no increasing period of emission intensity by consecutive measuremenl and the relative standard deviation among chips was less than 20%. The sensitivity of emission intensity for Na and K were proportional to the applied voltage, but Ca wasexponential. The sensitivity was different by kinds of element and applied voltage. According to its reproducibility, the spectrometer would be used for quantitative analysis.Permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/3115